Frank Reade, Jr.'s New electric submarine boat the Explorer to the North Pole under the ice - Senarens, Luis, 1863 - 1939
One in a series of boy's adventure stories centred round Frank Reade Jr., a young inventor-genius who created a robot, "Steam Man" and a succession of creatures including "Steam Horse", "Electric Dolphin" and innumerable flying and swimming wonders, including an electric airship, the "Eclipse". Aldine Romance of Invention, Travel, and Adventure Library, no. 16 Illustrated paper cover, printed in double columns.